Legal Knowledge Management System on Family Law for Society - Nur Putri Hidayah; Galih Wasis Wicaksono (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem: Until 2018, the problem in the realm of family law (marriage and inheritance) were the highest problems faced in religious courts. Through the Community Program for Women and Children Care (Madupria), the family welfare movement of Sumbersekar Village (PKK Desa Sumbersekar) wants to help in speaking out about the family’s legal problems that have been faced by the community in Sumbersekar village. Family legal issues in the community can be diminished if the community has good legal knowledge (intelligent legal). Nowadays, the current digital, legal collaboration, and information technology, should be utilized. One of the ways is through a legal knowledge management system, which will create a family legal savvy community in Sumbersekar village.Purpose/Objective Study: The purpose of this research is to perceive why family law problems occur in the village of Sumbersekar, and what kind of family law knowledge is needed, as well as modeling cases through a legal knowledge management system.Design/Methodology/Approach: This is multidisciplinary research that uses sociological legal research method, as well as using the method of research and development in the field of information technology.Findings: Family law issues in these cases are the rights and obligations of husband and wife and the distribution of inheritance. The causes of legal problems that happened regarding the rights and obligations of husband and wife are economic problems (10%), lack of education (20% lack of knowledge), poor communication (25%), and adverse environmental impacts (45%). In comparison, the problem of inheritance is caused by internal personal desires on controlling legacy (40%) and the lack of education/knowledge (60%). Whereas, the required legal experience to overcome these issues are family law and inheritance law is consisting of statutory regulations, judges’ decisions, and scientific articles.